Survival of Patients with Thyroid Cancer in Yazd, Iran - Ardakani, Hassan Ali Vahedian (Asian Pac J Cancer Prev, 2017)
BACKGROUND: Thyroid cancer is the most common endocrine related malignancy in the world. This cancer has increased during recent years in Iran and is the11th most common malignancy in Iranian population. Survival of patients with thyroid carcinoma in the different geographic areas within Iran is not clear. The present study aimed to estimate survival of patients suffering from thyroid cancer in Yazd, Iran. METHODS: In this retrospective cohort study, data were collected from 80 patients with thyroid cancer registered in Shohadaye Kargar and Shahid Sadoughy hospitals in Yazd between March 2001 and March 2012. The Kaplan-Meier analysis was used for estimation of survival over time and Cox regression method was performed for calculating hazard ratios according to demographic and risk variables. RESULTS: Survival rates at the end of 1, 3, and 5 years in thyroid cancer patients were 99%, 96%, and 91%, respectively. A statistically significant correlation was found between stage of disease, type of cancer and survival time of patients (p<0.05). The worst survival was in peoples with the anaplastic type and stage IV of thyroid carcinoma. CONCLUSION: The survival of patients with thyroid carcinoma was higher than some areas in Iran. Since type and stage of thyroid cancer were the important factors in survival time, screening of people for cancer diagnosis in early stages, it seems to improve survival of patients. Radioactive iodine therapy can increase the survival rate in patients suffering from thyroid malignancy.